1995 Neurospora bibliography - J. C. Schmit (Fungal Genetics Reports, 1995)
Every attempt has been made to insure that the citations appear exactly as they do in the original publication. Entries for which the original could not be obtained for verification are indicated by (-). Copies of the bibliography are available on computer discs (please indicate format needed) or by E mail. It can also be read/obtained from the FGSC WWW site.